Unequal Labour Market Impacts of COVID-19 in Sweden – But Not Between Women and Men - Pamela Campa; Jesper Roine; Svante Strömberg (Intereconomics, 2021)
So, when asked if men and women in the Swedish labour market have been differently affected by the COVID-19 pandemic, our overall conclusion would have to be "no".
Keywords: 330; Epidemie; Coronavirus; Arbeitsmarkt; Geschlechterunterschiede; Schweden